Multifunctional reversible outerwear design - Ibharim, Mohammad Shafirul Riza; Saleh, Maarof; Saleh, Nasyirah (2025)
The apparel overconsumption has impacted the lifespan of the garments, instead of being recycled or repurposed. This research explores the design and innovation of multifunctional outerwear that can transform into different types of clothing. This design aims to meet the growing demand for versatile, stylish, and practical clothing. This study focuses on enhancing outerwear functionality through reversible design elements and transformability, offering consumers greater flexibility and sustainability in wardrobe choices. The methodology integrates design experimentation with technical garment construction, employing a multifunctional clothing technique using several fastenings that enable seamless transitions between garment forms. Fabric selection and fastening placement were strategically analyzed to ensure aesthetic appeal and functional integrity. The reversible feature further amplifies the versatility of the outerwear, allowing multiple styling options from a single garment. This multifunctional design contributes to sustainable fashion by reducing the need for various garments and supporting conscious consumer behavior. The study contributes to sustainable fashion by demonstrating functional clothing that can be worn for different styles and occasions and is suitable for daily activities. It offers thoughtful design and innovative construction techniques that can lead to adaptable fashion solutions that align with modern lifestyle needs and environmental concerns.